Heat Stress and Feed Restriction Distinctly Affect Performance, Carcass and Meat Yield, Intestinal Integrity, and Inflammatory (Chemo)Cytokines in Broiler Chickens - Emami, Nima K.; Greene, Elizabeth S.; Kogut, Michael H.; Dridi, Sami (Frontiers in Physiology, 2021)
This study was conducted to distinguish the effects of heat stress (HS) and feed intake (FI) on broiler chicken’s physiological responses. Day-old male Cobb 500 broilers (n = 672) were allocated to three treatments: (1) control (CTL): birds raised under normal temperature (23°C) from day 29 to 42; (2) cyclic heat stress (CHS): birds exposed to high temperatures (8 h/day at 35°C; from 9:30 am to 5:30 pm) from day 29 to 42; (3) pair-fed (PF): birds raised under thermoneutral condition but fed the same amount of feed as CHS from day 29 to 42. On day 42, 15 birds/pen were processed, to measure carcass and meat yields. To measure blood parameters and gut integrity (using fluorescein isothiocyanate-dextran), on day 42, CHS birds were sampled before (Pre-CHS) and 2 h after (Post-CHS) the temperature increased. Furthermore, after sampling CTL birds, they were exposed to 2h heat and sampled (acute heat stress, AHS). Data were analyzed using one-way ANOVA (JMP Pro15) and significance between treatments identified by LSD (P < 0.05). BW and relative carcass yield were significantly higher in CTL compared to CHS and PF. Compared to CHS, PF had significantly higher BW and lower relative carcass yield. Breast yield was significantly higher for CTL and PF, while leg quarters and wings yield were significantly lower compared to CHS. Gut barrier integrity was significantly altered in Post-CHS and AHS compared to CTL. mRNA abundances of tumor necrosis factor-α, C-C motif chemokine ligand-20, heat shock protein (HSP)-27, and HSP70 were significantly higher in Post-CHS and AHS compared to CTL. AHS had significantly higher mRNA abundances of CARD domain containing (NLRC)-3 and NLRC5 inflammasomes, and lower superoxide dismutase (SOD)-1 and SOD2 abundance compared with CTL. PF had significantly higher liver weight (% BW) compared to all other groups; while abdominal fat was significantly higher in Pre-CHS compared to CTL, PF, and AHS. Together, these data indicate that the negative effects of HS are partially due to reduced FI. However, the negative effect of HS on gut integrity, average daily gain, feed conversion ratio, and meat yield are direct and independent of the reduced FI during the HS. Thus, warrant investigating the underlying mechanisms in future research.